Pengentasan Kemiskinan Nasabah BTPN Syariah Penerima Program Daya Berdasarkan Peningkatan Kinerja dan Keberlanjutan Usaha Melalui Pendampingan Program Bestee - Reny Fitriana Kaban; Ai Nety Sumidartini (CV. Kalimasada Group, 2025)
Poverty is still a global challenge, including in Indonesia, although a decline in the number of poor people has occurred in recent years. Community empowerment programs are one of the important strategies to address this issue. BTPN Syariah launched the Daya Program, which aims to improve the welfare of female customers through sharia financing and business mentoring. However, to ensure the sustainability and improvement of customers' business performance, more intensive mentoring is needed. The Bestee program comes as a solution by involving university students in providing business mentoring to customers. This study aims to analyze the effectiveness of the Bestee program in improving the performance and sustainability of BTPN Syariah customers who receive the Daya program. The research methodology uses a descriptive qualitative approach with SWOT analysis of two customers and evaluation of the level of customer satisfaction post-mentoring. Primary data was collected through direct observation and interviews, while secondary data was obtained from BTPN Syariah's sustainability reports and relevant literature. The results show that mentoring by Bestee facilitators provides positive benefits for customers. They were satisfied and able to understand the materials provided. Although there has not been a significant increase in turnover over a month, the mentoring helps customers in terms of digital promotion, financial recording, and business identity.